MODEL LAPS (LOGAN AVENUE PROBLEM SOLVING)-HEURISTIC BERBASIS CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA - Alibas, Fadhila; Agung, Afiq; Hutapea, Bilferi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
One of the most important skills to be mastered by students in the rapid development of 21st century technology is the ability to solve problems. One of the innovations in improving students' problem-solving abilities is the implementation of the LAPS-Heuristic Based on CRT model. This study aims to describe the effect of the CRT-Based LAPS Heuristic learning model on students' physics problem-solving abilities. This type of research is a quasi-experimental study with a